Diabetes Self Care, Resilience and Quality of Life among Patients with Type II Diabetes: Self Care, Resilience and Quality of Life among Patients with Type II Diabetes - khan, zahra; kazmi, Umm E Rubab (Pakistan Journal of Health Sciences, 2022)
Diabetes is highly prevalent disease in Pakistan, and it greatly impacts the quality of life of its patients. Diabetes self-care and resilience can be significant in this regard. Objective: To find out the relation among diabetes self-care, resilience, and quality of life in patients with type II diabetes. Methods: The correlation research design was used along with purposive sampling to select the sample (N=200) from Government and private hospitals of Lahore. 11 items Summary Diabetes Self-care Activity scale (SDSCA), 18 items Trait Resilience Scale (TRS) and 15 items Diabetes Quality of Life (DQOL) scale were used in the study. Researchers translated English versions of TRS and DQOL scales into Urdu language following the Lexion Equivalence method of translation. Results: Correlation analysis revealed significant positive relation between general diet and resilience (.61, p< 0.5), Blood glucose and resilience (.53, p < 0.5) and between resilience and quality of life (.77, p<0.5). Multiple linear regression revealed that self-care activities significantly predict quality of life. Conclusions: The more the patients are following self-care activities, the better will be their quality of life. The study will be helpful for clinical psychologists to boost the resilience of patients with diabetes